Front Matter (Journal of the Assembly for Expanded Perspectives on Learning, 2002)
Editors' Message In his essay Two Kinds of Thinking Carl Jung describes direct and indirect thinking. Associated with language, direct thinking’s premier ability is parsing and defining reality so that we might work on that reality and act in the world. Associated with imagery, dreaming, and story telling, indirect thinking taps the realm of mythos where we dwell in fantasies and paradoxes. Indirect thinking is neither a contradiction nor denial of rationality. Rather, it is thinking that operates by a different logic, one capable of offering different insights, different versions of possible realities. Jung’s two kinds of thinking reflect a similar division in teaching: direct and indirect. Direct teaching is forthright instruction in the processes, canons, and rationality of writing and reading. Indirect teaching, far less privileged because far less accessible to quantification and to clear articulation, is teaching on the slant, teaching that accesses the mythic dimensions of writing and reading by inviting stories, courting paradoxes, and contradicting system. In this issue we celebrate mythos, the realm of indirect thinking, and the value derived from teaching, thinking, reading, and writing on the slant. Mythos bears a special power in Western culture. Once upon a time in ancient Greece, our classical forebearers organized their lives around reverberations of imagination, resonating to the power of narrative. Characteristic of the sophists, truth was created not out of Aristotelian hypotactic logic, but out of the analogic, mimetic logic of stories, of indirect thinking (see Jarratt). In the early 18th century, a time dominated by Cartesian rationalism in education, Giambattista Vico ascribed a central role to mythos, for only within imagination can young minds discover new and original thoughts. The tug of mythos unravels the neatly woven fabric of Western rationality to the extent that James Baumlin and Tita French Baumlin claim it as the fourth pistis, the fourth proof, rounding out the Aristotelian trio of logos, pathos, and ethos. They argue that “[t]he mythic seeks [. . .] to unite, to synthesize, to assert wholeness in multiple or contrasting choices and interpretations. Mythos thus offers a synthetic and analogical, as opposed to analytic, mode of proof, one that discovers—indeed, celebrates—the diversity of truth” (106). Mythos affords insight into truths unavailable through other more direct modes of knowing, holding the hope of transcendence, of healing, of serendipity. The essays in this issue celebrate mythos and emphasize the necessity of teaching on the slant. We open with James Moffett, Lit Crit and Holy Writ, a keynote address presented in 1995 at the first AEPL summer conference held in Snow Mountain, Colorado. Edited by Charles Suhor, Moffett’s exploration of the connection between literacy criticism and religious exegesis emphasizes the transcendental quality of stories, the ability of stories to move us above and beyond our current lives. Gina Briefs-Elgin in Something to Have at Heart highlights the role of memory in just such a transcendental endeavor. Briefs-Elgin argues that entrusting beautiful writing to heart enriches and empowers life, providing our students and us with new ways to shape and cope with life. Protean as it is, mythos offers insights into the healing, as well as the transcendent, power of stories. As Baumlin and Baumlin argue, mythos is iatrological, “a healing story, a means of participation in the rhythm of the universe, in its contrasting joys and pains” (107). Christopher Weaver in The Rhetoric of Recovery and Brenda Daly in Stories of Re-Reading explore the connection between healing and narratives, finding in story telling the rituals and emotional resonance necessary for healing and for effective teaching. Tapping his own struggles with addiction, Weaver offers the rituals of Alcoholics Anonymous as a template for teaching transformation through writing. In her concern with her students’ emotional engagement with fiction, Daly explores and advocates the value of disclosure, of interweaving literature, response, and life stories as a means of fostering connections and insights. The third value that mythos offers is the gift of surprise, the gift of serendipity, or happy discovery. Devan Cook in Successful Blunders points to the importance of mistakes in the classroom, arguing that through our “blunders” we may stumble on our most teachable moments. Terence Riley in The Accidental Curriculum explores the importance of accident, of mythic indirection, in curricular reform, arguing that neither preparation nor organization will ensure “the bright moments” of learning we hope will happen. Instead, we must rely on an element of chance to animate our teaching and our students’ learning. Finally, mythos invites us to participate in the world differently, to listen to ourselves and others with an intensity that opens us up to the voice of the soul. So argues Robbie Pinter. In The Landscape Listens—Hearing the Voice of the Soul, she draws on Mary Rose O’Rielley’s concept of “radical listening” to advocate a classroom approach that enables students to “listen to their lives.” Weaving through language and rhetoric, mythos does not deny the law of logic or the constraints of reality; rather, it offers an alternative logic, an array of different, possible realities. Manifested in poetry, in narrative, in performances of art, in all acts of dreaming, mythos enables us to think, teach, write, and read on the slant, affording us insights otherwise unavailable through the frontal assault of logos. This gift is indeed cause for celebration. Works Cited Jarratt, Susan C. Rereading the Sophists: Classical Rhetoric Refigured. Carbondale, IL: Southern Illinois UP, 1991. Jung, Carl Gustav. Two Kinds of Thinking. Selected Writings. New York: Book-of-the- Month, 1997. 5-31. Baumlin, James S., and Tita French Baumlin. On the Psychology of the Pisteis: Mapping the Terrains of Mind and Rhetoric. Ethos: New Essays in Rhetorical and Critical Theory. Dallas: Southern Methodist UP, 1994. 91-112.